2008
DOI: 10.4054/mpidr-wp-2008-023
|View full text |Cite
|
Sign up to set email alerts
|

Being born under adverse economic conditions leads to a higher cardiovascular mortality rate later in life: evidence based on individuals born at different stages of the business cycle

Abstract: Working papers of the Max Planck Institute for Demographic Research receive only limited review. Views or opinions expressed in working papers are attributable to the authors and do not necessarily reflect those of the Institute. Being born under adverse economic conditions leads to a higher cardiovascular mortality rate later in life: evidence based on individuals born at different stages of the business cycle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Some previous research has suggested that early-life conditions may be more critical than period conditions for old-age mortality (Finch and crimmins 2004) or that, even if period conditions are more important, early-life conditions proxied by a cohort's early mortality could still have a key role (barbi and vaupel 2005). this study adds to the accumulating evidence suggesting that at the cohort level, early-life mortality conditions may not be a critical predictor of adult and old-age mortality (bruckner and catalano 2009; Gagnon and mazan 2009;van den berg, doblhammer, and christensen 2009). the findings of this study are also consistent with murphy (2010), who finds that period factors may be more important than cohort factors in determining mortality.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Some previous research has suggested that early-life conditions may be more critical than period conditions for old-age mortality (Finch and crimmins 2004) or that, even if period conditions are more important, early-life conditions proxied by a cohort's early mortality could still have a key role (barbi and vaupel 2005). this study adds to the accumulating evidence suggesting that at the cohort level, early-life mortality conditions may not be a critical predictor of adult and old-age mortality (bruckner and catalano 2009; Gagnon and mazan 2009;van den berg, doblhammer, and christensen 2009). the findings of this study are also consistent with murphy (2010), who finds that period factors may be more important than cohort factors in determining mortality.…”
Section: Discussionsupporting
confidence: 82%
“…it is possible that early-life conditions exert important influences on cohorts' laterlife mortality, but that early-life mortality conditions generally do not capture the important aspects of early-life conditions. For example, van den berg and colleagues (van den berg, lindeboom, and Portrait 2006;van den berg, doblhammer-Reiter, and christensen 2008;van den berg, doblhammer, and christensen 2009) found that early-life macroeconomic conditions predict cohorts' later mortality: being born in a recession, for example, increases later mortality. cutler, miller, and norton (2007), however, did not identify any health effects in later life for persons born during the depression of the 1930s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there may exist local and transitory determinants of long-run outcomes that also covary with ambient air pollution. For example, local economic conditions are both strong predictors of ambient TSP (Chay and Greenstone, 2003b) and have been shown to affect infant health and fertility decisions (Dehejia and Lleras-Muney, 2004;Lindo, 2011;Schaller, 2012) as well as long-run mortality (Van den Berg et al, 2011;Van Den Berg et al, 2006). Any unobserved transitory local shocks that covary with both TSP and long-run outcomes will lead to bias in the OLS estimate of β 1 .…”
Section: Econometric Specification Baseline Econometric Modelmentioning
confidence: 99%
“…Therefore, disturbances in the initial health capital during this critical period could lead to disruptions in the pathways of later-life outcomes. For instance, studies document negative short-term and long-term consequences of in-utero and early-life exposures to income shocks, agricultural crop failure, pollution, natural disasters, stress, toxic chemicals, and nutritional shocks (Baird et al, 2016;Billings & Schnepel, 2018;Lindeboom et al, 2010;Sanders, 2012;Scholte et al, 2015;Torche, 2018;van den Berg et al, 2011). These prenatal and early life shocks can be translated into adverse health outcomes during infancy and early childhood, which in turn appear in a wide array of medium-run and long-run outcomes, including cognitive development (Aizer et al, 2016;Berthelon et al, 2021), test scores (Sanders, 2012;Shah & Steinberg, 2017), educational attainments (Almond et al, 2009;Fuller, 2014), adulthood earnings (Behrman & Rosenzweig, 2004;Black et al, 2007), health during adulthood (Maruyama & Heinesen, 2020), hospitalization during adulthood (Miller & Wherry, 2019), and later-life old-age mortality outcomes (Goodman-Bacon, 2021;van den Berg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%